Extensive Ethnic Variation and Linkage Disequilibrium at the FCGR2/3 Locus: Different Genetic Associations Revealed in Kawasaki Disease - Nagelkerke, Sietse Q.; Tacke, Carline E.; Breunis, Willemijn B.; Tanck, Michael W. T.; Geissler, Judy; Png, Eileen; Hoang, Long T.; van der Heijden, Joris; Naim, Ahmad N. M.; Yeung, Rae S. M.; Levin, Michael L.; Wright, Victoria J.; et al. (Frontiers in Immunology, 2019)
The human Fc-gamma receptors (FcγRs) link adaptive and innate immunity by binding immunoglobulin G (IgG). All human low-affinity FcγRs are encoded by the FCGR2/3 locus containing functional single nucleotide polymorphisms (SNPs) and gene copy number variants. This locus is notoriously difficult to genotype and high-throughput methods commonly used focus on only a few SNPs. We performed multiplex ligation-dependent probe amplification for all relevant genetic variations at the FCGR2/3 locus in >4,000 individuals to define linkage disequilibrium (LD) and allele frequencies in different populations. Strong LD and extensive ethnic variation in allele frequencies was found across the locus. LD was strongest for the FCGR2C-ORF haplotype (rs759550223+rs76277413), which leads to expression of FcγRIIc. In Europeans, the FCGR2C-ORF haplotype showed strong LD with, among others, rs201218628 (FCGR2A-Q27W, r2=0.63). LD between these two variants was weaker (r2=0.17) in Africans, whereas the FCGR2C-ORF haplotype was nearly absent in Asians (minor allele frequency <0.005%). The FCGR2C-ORF haplotype and rs1801274 (FCGR2A-H131R) were in weak LD (r2=0.08) in Europeans. We evaluated the importance of ethnic variation and LD in Kawasaki Disease (KD), an acute vasculitis in children with increased incidence in Asians. An association of rs1801274 with KD was previously shown in ethnically diverse genome-wide association studies. Now, we show in 1028 European KD patients that the FCGR2C-ORF haplotype, although nearly absent in Asians, was more strongly associated with susceptibility to KD than rs1801274 in Europeans. Our data illustrate the importance of interpreting findings of association studies concerning the FCGR2/3 locus with knowledge of LD and ethnic variation.